RELATIONSHIP BETWEEN TEACHER TEACHING CREATIVITY AND STUDENT LEARNING OUTCOMES IN MATHEMATICS IN CLASS V SDN 14 BUNGKU DURING THE COVID-19 PANDEMIC - Fiska Ariyanti; Akina Akina; Nuraini Nuraini (Jurnal Dikdas, 2021)
This The problem in this study is whether there is a relationship between teacher teaching creativity and student learning outcomes in mathematics class V SDN 14 Bungku during the Covid-19 pandemic. This study aims to determine the relationship between teacher teaching creativity and student learning outcomes in mathematics in grade V SDN 14 Bungku during the Covid-19 pandemic. The subjects of this study were all fifth grade students of SDN 14 Bungku with a total of 16 students. This research is a quantitative study, the design used in this study is a correlation design. The instruments used in data collection were observation, questionnaires and documentation. Student learning outcomes data were obtained from the students' daily test scores on fractions. The results of the research data analysis showed that: (1) The teaching creativity of teachers at SDN 14 Bungku during the Covid-19 pandemic was included in the very good category, there were 15 students or 93.75% who stated that the teacher's teaching creativity was very high and 1 student or 6, 25% stated that the teacher's teaching creativity was high. (2) Student learning outcomes in mathematics class V are included in the good category, there are 11 students or 68.75% of students whose mathematics learning outcomes get a very good predicate and 5 students or 31.25% students whose mathematics learning outcomes get a good predicate. (3) There is a significant relationship between teacher teaching creativity and student learning outcomes in mathematics. This can be seen from the acquisition of rcount> rtabel = 0.5151> 0.4973 at the 95% significance level or α = 0.05 and n-2 = 14 (16-2). The value of this correlation coefficient if interpreted at the interpretation value of the correlation coefficient can be categorized as "moderate" in the level of influence. Based on this, the hypothesis (H1) is "accepted", thus there is a relationship between teacher teaching creativity and mathematics learning outcomes for fifth grade students of SDN 14 Bungku during the Covid-19 pandemic.